Electrogenerated Chemiluminescence Biosensor with Gold Nanoparticles/Ru(bpy)32+ Multilayer Films on Gold Electrodes for the Determination of Ephedrine Hydrochloride - Ma, Lifeng; Wang, Li; Liu, Lijun; Kang, Longli (Asian Journal of Chemistry, 2012)
The aim of this study presented here is to develop a novel method for the determination of ephedrine hydrochloride with the electrogenerated chemiluminescence (ECL) by using gold nanoparticles/tris(2,2'-bipyridyl)dichlororuthenium(II) (AuNPs/Ru(bpy)32+) multilayer films modified gold electrode. The ECL active species, Ru(bpy)32+ was immobilized into the {AuNPs/Ru(bpy)32+}n multilayer films by layer-by-layer assembly, which is based on the electrostatic interaction between positively charged Ru(bpy)32+ and negatively charged AuNPs. The novel multilayer films modified gold electrode was characterized by cyclic voltammetry, ECL and SEM. The ECL biosensor based on the multilayer films containing Ru(bpy)32+ was used for ECL determination of ephedrine hydrochloride. The ECL intensity was correlated with the ephedrine hydrochloride concentration in the range from 2.0 × 10-7-1 × 10-4 g/mL (R = 0.9978) and the detection limit was 7.0 × 10-8 g/mL. The relative standard deviation (n = 11) was 3.2 % for detecting 2.0 × 10-6 g/mL ephedrine hydrochloride. This method has been applied successfully to determine ephedrine hydrochloride in pharmaceutical preparations and in ephedra herb. Statistical analysis (Student's t-test and variance ratio F-test) of the obtained results showed no significant difference between the proposed method and the reference method.